THE NATURE AND ORIGIN OF AUTHIGENIC CHLORITE AND RELATED CEMENTS IN OLIGO–MIOCENE RESERVOIR SANDSTONES, TAPTI GAS FIELDS, SURAT DEPRESSION, OFFSHORE WESTERN INDIA. (October 2015) - Huggett, J. M.; Burley, S.D.; Longstaffe, F. J.; Saha, S.; Oates, M. J.
<x xml:space="preserve">Abstract</x> Reservoir sandstones in the Mid‐ and South Tapti gas fields in the Surat Depression (Mumbai Offshore Basin, western India) have been investigated using a range of petrographic techniques, isotope geochemistry and basin modelling. Authigenic chlorite is abundant in the shallow‐marine sandstones of the Miocene Mahim Formation, a major reservoir rock in the Mid‐ and South Tapti fields, which are described here in terms of their quality and diagenetic characteristics. The sandstones are currently at burial depths of between ∼1500 and 2800m. The authigenic chlorite has had a significant impact on the resulting reservoir quality of the sandstones and is interpreted to have originated as odinite clay of the verdine facies that replaced faecal or pseudo‐faecal pellets, together with volumetrically small but abundant grain coatings and grain rims, and formed at the site of major riverine iron influx onto the shallow‐marine shelf during periods of relatively low sea level. Pellets have been variably compacted to form pseudomatrix. Reservoir sandstones from similar depositional settings on the west coast of India or other sub‐tropical settings are likely to exhibit comparable diagenetic effects on reservoir quality. Compositionally, the chlorite is the iron‐rich form known as chamosite. The chemistry of all the chlorite morphologies is the same in all studied samples. Oxygen isotope analyses of carbonate cements in the Mahim Formation sandstones have provided an approximate temperature framework for diagenesis of the non‐carbonate cements. Oxygen isotope results for the chlorite, however, suggest much higher temperatures than its position in the paragenetic sequence would warrant. These results suggest that the clay formed first as 1:1 layer clays, in this case odinite, which were then transformed to Fe‐chlorite as burial depths and temperatures increased. Reservoirs in the Mahim, Daman and Mahuva Formation sandstones are thus greatly influenced by the diagenesis of authigenic chlorite and locally by the precipitation of carbonate cements. Reservoir quality is good where thick, continuous chlorite rim cements are present and where chlorite pellets are sufficiently indurated for them not to be compacted. Chlorite rim cements have reduced the extent of quartz overgrowth cementation in the sandstones.